2021
DOI: 10.1002/14651858.cd004265.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Hand-washing promotion for preventing diarrhoea

Abstract: Background Diarrhoea accounts for 1.8 million deaths in children in low‐ and middle‐income countries (LMICs). One of the identified strategies to prevent diarrhoea is hand washing. Objectives To assess the effects of hand‐washing promotion interventions on diarrhoeal episodes in children and adults. Search methods We searched CENTRAL, MEDLINE, Embase, nine other databases, the World Health Organization (WHO) International Clinical Trial Regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 130 publications
(5 reference statements)
0
29
1
Order By: Relevance
“…In the finger route, pathogens are transmitted from the original host's feces to food or directly to a new host via hand contact. Systematic reviews have supported these results by finding that hand washing with soap has a protective effect against diarrhea diseases (41). However, studies in Bangladesh have shown that, among cholera patients, there is a low frequency of hand washing with soap (7%) after toilet visits (42).…”
Section: The Fecal-oral Route (Secondary Transmission)mentioning
confidence: 99%
“…In the finger route, pathogens are transmitted from the original host's feces to food or directly to a new host via hand contact. Systematic reviews have supported these results by finding that hand washing with soap has a protective effect against diarrhea diseases (41). However, studies in Bangladesh have shown that, among cholera patients, there is a low frequency of hand washing with soap (7%) after toilet visits (42).…”
Section: The Fecal-oral Route (Secondary Transmission)mentioning
confidence: 99%
“…During conflicts, children under the age of five are twenty times more likely to die from diarrhoeal diseases rather than as a direct consequence of violence [1]. Handwashing with soap is considered to be one of the most cost-effective public health interventions [2] and has the potential to reduce diarrhoea by 23% to 48% [3][4][5][6][7]. However, the prevalence of handwashing with soap after contact with excreta is estimated to be 19% globally, and prevalence is even lower at other critical times (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The hygiene in rural India is poor. Cochrane review [23] stated that hand washing could reduce the incidence of diarrhea by about 30% mainly among those in lowmiddle income countries and high-income countries. The vector borne diseases [mosquitoes] are bound to affect the region and it is of great concern in India [3].…”
Section: Venkatraman Et Almentioning
confidence: 99%